Effect of surface electromagnetic wave treatment on the refractive properties of thin films based on indium tin oxides with laser-deposited single-walled carbon nanotubes - A. S. Toikka; N. V. Kamanina (Российский технологический журнал)
Objectives. The article investigates the effect of surface electromagnetic wave (SEW) treatment on the refractive properties of thin conducting films based on indium tin oxide (ITO) with laser-deposited single-walled carbon nanotubes (CNTs). The effective thickness of the layer of laser-deposited CNTs before and after SEW treatment is evaluated.Methods. A laser-oriented deposition method employing a CO2 laser (λ = 10.6 µm) was used to form the structures. Diagnostics of modifications of ITO thin films were carried out using an ellipsometer operating in the spectral range of 300–1000 nm. The Cauchy model was used to describe the optical properties of K8 crown substrates and ITO thin films. To interpret the ellipsometry results of ITO modifications with CNTs, an effective-thickness virtual layer model was introduced. During post-processing of the surface, a CO2 marker (λ = 10.6 µm) was used to generate SEW. The influence of SEW treatment on the thickness of the virtual layer was assessed using ellipsometry and atomic force microscopy in contact mode.Results. Based on the ellipsometry data, the effective thickness of the CNT layer was in the range of 24–26 nm. Following SEW treatment, the thickness of the effective CNT layer decreased to 4–8 nm, indicating the possibility of precision processing of the ITO surface with CNTs using SEW. When CNTs are deposited on an ITO surface with subsequent SEW treatment of the surface, reflection losses for p-polarized radiation are reduced. In a spectral range of 400–750 nm at an angle of incidence relative to the normal to the plane of structures α = 65°, a decrease in reflection is observed from 18.5% to 13.5% relative to ITO without CNTs and SEV treatment; at α = 71°, a decrease from 6.4% to 4.7% is observed; at α = 77°, a decrease from 1.8% to 1.2%.Conclusions. For ITO-based thin films with laser-deposited CNTs, the described SEW treatment method provides a precise reduction in the thickness of the composite structure while preserving the antireflective properties of the CNTs. These capabilities make it possible to use the studied ITO modifications in solving problems in optical electronics, microfluidics, and biomedicine.